Retorika Komunikasi Aa Gym dalam Kajian Al-Hikam “Jangan Sia-Siakan Waktu” - Yousef Bani Ahmad (Program Studi Magister Linguistik Terapan UNJ, 2022)
The purpose of this study is to find out what the rhetorical element in Aa Gym's oral discourse looks like when delivering its da'wah message to the congregation regarding the study of Al-Hikam with the topic “don't waste time